Exciton and Charge Generation in PC60BM Thin Films - Stoichko Dimitrov (The Journal of Physical Chemistry C, 2017)
Transient absorption spectroscopy is employed to contrast the photophysics of [6,6]-phenyl C61 butyric acid methyl ester (PC60BM) dispersed in a polystyrene matrix and as a neat film. For the dispersed PC60BM:polystyrene film, singlet excitons are observed that undergo intersystem crossing to triplet excitons. In contrast, in the neat PC60BM film, the transient absorption data indicate significant polaron generation, with photogenerated polarons exhibiting dispersive, bimolecular charge recombination on the nano- to microsecond time scales. These results are discussed in terms of their implications for charge generation from PC60BM light absorption in polymer/fullerene solar cells.